CORONAVIRUS DISEASE 2019 AND MUCORMYCOSIS A GLOBAL THREAT: A SYSTEMIC REVIEW - BISWAS, BIKASH; PRAMANIK, INDRANI; MANDAL, SANJUKTA; SINGHA ROY, POULAMY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: According to the recent studies, it is seen that coronavirus disease 2019 (COVID-19) infection is associated with many bacterial and fungal infections. In case of COVID-19 patients, diabetes mellitus (DM) and hypertension (HTN) are the prime risk factors and during the course of treatment, patients develop secondary fungal infections like mucormycosis. We conducted a systemic review of the present scenario and tried to evaluate the association of mucormycosis with COVID-19. Methods: We searched articles related to the COVID-19 associated mucormycosis, in PubMed, IndMed, and Cochrane Library. We conducted a meta-analysis on the basis of systemically reviewed all articles which reported COVID-19 associated with mucormycosis. We analyzed comorbidity, treatment, and outcome of patients in association with COVID-19 and mucormycosis. Results: We found a total of 196 articles based on mucormycosis, out of which only 25 were selected on the basis of our inclusion and exclusion criteria. 71 cases were found and most of the cases were from India and USA. We also found that it was more prevalent among male patients and patients with DM, and in association with HTN. Conclusion: It is seen from the studies that patients already suffering from DM and HTN when infected with coronavirus are most likely to develop mucormycosis. Treatment of latent DM, prediabetic patients, conversely, that efforts to diagnose, detect, and treat DM may have a beneficial influence in the treatment of secondary fungal infections like mucormycosis. Finding out all the cases of DM and treatment of DM can carry out an advantageous effect in all patients suffering from COVID-19.